2017
DOI: 10.12697/fce.2017.54.11
|View full text |Cite
|
Sign up to set email alerts
|

New records of lichens and allied fungi from the Leningrad Region, Russia. VIII

Abstract: Thirteen species and one variety of lichens, nine lichenicolous and two saprobic fungi are reported for the first time for St. Petersburg, the whole Leningrad Region or its western or eastern parts. The lichens Bacidina brandii, B. neosquamulosa, Porina leptalea, Rinodina aspersa and the lichenicolous fungus Scutula dedicata are reported for the first time for Russia, lichenicolous fungus Lichenoconium aeruginosum -for European Russia, the lichen Tetramelas chloroleucus, lichenicolous fungi Lichenoconium pyxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…The present paper continues the series of publications on new and noteworthy findings of lichens and allied fungi from the Leningrad Region and St. Petersburg (see e.g. Kuznetsova et al, 2007Kuznetsova et al, , 2012Stepanchikova et al, 2010Stepanchikova et al, , 2011Himelbrant et al, 2014Himelbrant et al, , 2016Himelbrant et al, , 2017. Skyttea gre garia and Xylographa septentrionalis are reported for the first time for Russia, Didymellopsis col lematum, Intralichen lichenicola and Xylographa pallens are new for the North-Western European Russia.…”
Section: Introductionsupporting
confidence: 76%
“…The present paper continues the series of publications on new and noteworthy findings of lichens and allied fungi from the Leningrad Region and St. Petersburg (see e.g. Kuznetsova et al, 2007Kuznetsova et al, , 2012Stepanchikova et al, 2010Stepanchikova et al, , 2011Himelbrant et al, 2014Himelbrant et al, , 2016Himelbrant et al, , 2017. Skyttea gre garia and Xylographa septentrionalis are reported for the first time for Russia, Didymellopsis col lematum, Intralichen lichenicola and Xylographa pallens are new for the North-Western European Russia.…”
Section: Introductionsupporting
confidence: 76%
“…This paper continues the series of publications focused on new and noteworthy findings of lichens and allied fungi from the Leningrad Region and St. Petersburg (see, e.g., Stepanchikova et al, 2010Stepanchikova et al, , 2018Kuznetsova et al, 2012;Himelbrant et al, 2016Himelbrant et al, , 2017 This paper contains data on the groups of species that are difficult to identify. Most of the records originate from remote places in the Leningrad Region.…”
Section: Introductionmentioning
confidence: 52%
“…J. Gerasimova (LECB). -New to WLR, known from SPb (Himelbrant et al, 2017). Distribution in North-Western European Russia outside of LR: not reported.…”
Section: The Speciesmentioning
confidence: 98%
“…New to LR. Recently published from St. Petersburg (Stepanchikova et al, 2015), but the specimens were re-identified (see Himelbrant et al, 2017 (Zhurbenko, 2010). Distribution in Fennoscandia: Sweden, Norway (Nordin et al, 2011); not recorded in Baltic countries.…”
Section: Methodsmentioning
confidence: 99%